Visual attention and response time to distinguish athletes from non-athletes: A virtual reality study - Lucia Imperiali; Stefano Borghi; Sara Bizzozero; Elena Prandoni; Ambra Bisio; Antonio La Torre; Roberto Codella (PLoS ONE, 2025)
In recent years, cutting-edge technologies have been increasingly integrated into sports to assess physical and cognitive capacities. Virtual Reality (VR) technology has emerged as a powerful tool, offering an immersive and controlled scenario for examining cognitive functions. In light of the growing adoption of VR-systems, this study aimed to investigate the differences in visual attention and response time (RT) between athletes and non-athletes utilizing a VR-system and evaluate the discriminatory power of VR assessments towards the two groups. Sixty-one participants (Age: 22 ± 1.8years; athletes = 33, non-athletes = 28) underwent two visual attention evaluations through the Multiple Object Tracking (MOT) paradigm and three RT evaluations, all within a fully immersive VR environment. The visual attention assessments included the “MOT Assessment” (MOT), which did not have a primary target to select, and the “MOT, Primary Target Onset” (MOT-PT), which required selecting a primary target. The three RT evaluations included Continuous RT (RT-C), RT with Inter-Time between stimuli (RT-I), and Go No-Go RT (RT-GNG). In all RT assessments, participants aimed to touch the target that turned green in the shortest time as possible. In the RT-GNG test, participants responded to green targets by touching them with the hand controllers and refrained from touching red targets. No differences were found between athletes and non-athletes in visual attention tasks. However, athletes outperformed non-athletes in RT assessments (RT-C: 504.8 ± 45.9ms vs. 549.1 ± 45.6ms; p < 0.001. RT-I: 481.1 ± 44.9ms vs. 534.2 ± 58.6ms; p < 0.001. RT-GNG: 502.9 ± 38.8ms vs. 555.6 ± 57.8ms; p < 0.001). ROC curve analysis demonstrated moderate accuracy in differentiating athletes from non-athletes in RT assessments (RT-C: AUC = 0.75, p < 0.001; RT-I: AUC = 0.75, p < 0.001; RT-GNG: AUC = 0.80, p < 0.001). These findings underscore the significant role of RT in distinguishing athletes from non-athletes and highlight the discriminative potential of VR-systems as valuable tools in sports evaluation. Including RT assessments into traditional training regimens could offer new insights for evaluating athletic performance.